1994
DOI: 10.1021/bi00172a009
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Random Coil-.beta.-Sheet Transition of the Alzheimer .beta.-Amyloid Fragment (25-35)

Abstract: The beta-amyloid protein (39-43 amino acid residues) is the major constituent of the amyloid deposits found in brain of patients with Alzheimer's disease. Using circular dichroism spectroscopy, we have studied the secondary structure and the aggregation of fragment 25-35 of the beta-amyloid protein (beta AP(25-35)OH) under a variety of conditions. beta AP(25-35)OH in solution at pH 4.0 or 5.5 exhibits a concentration-dependent random coil<-->beta-sheet transition. The equilibrium is characterized spectroscopic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
222
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(241 citation statements)
references
References 22 publications
19
222
0
Order By: Relevance
“…For H17 (10 M), the ␤-sheet content is estimated as ϳ30% according to Greenfield and Fasman (29) in good agreement with computer simulations using the method of Yang et al (28). The concentration of monomers in solution, C A , is evaluated according to (36).…”
Section: Resultsmentioning
confidence: 99%
“…For H17 (10 M), the ␤-sheet content is estimated as ϳ30% according to Greenfield and Fasman (29) in good agreement with computer simulations using the method of Yang et al (28). The concentration of monomers in solution, C A , is evaluated according to (36).…”
Section: Resultsmentioning
confidence: 99%
“…1B). Ab25-35 does not occur naturally but has shown to mimic the effects of Ab1-42 [15][16][17]. Ab1-42, which occurs in a brain affected by AD, was more effective in cell proliferation than Ab25-35 (Fig.…”
Section: Ab Promotes Microglial Cell Proliferationmentioning
confidence: 98%
“…The initial neuronal responses to A␤ in cortical circuits and the regulation of A␤-induced signaling remain unclear. In this study, we found that exposure of cortical slices to A␤ or A␤ [25][26][27][28][29][30][31][32][33][34][35] induced a marked increase in the activation of protein kinase C (PKC) and Ca 2؉ /calmodulin-dependent kinase II (CaMKII), two enzymes critically involved in a variety of cellular functions. Activation of M1 muscarinic receptors, but not nicotinic receptors, significantly inhibited the A␤ activation of PKC and CaMKII.…”
mentioning
confidence: 99%